The SAFE strategy for the elimination of trachoma by 2020: will it work? - Bailey Robin; Lietman Tom (The World Health Organization, 2001)
WHO has recently launched a programme (GET 2020) for the elimination of trachoma, the leading cause of preventable blindness. GET 2020 has adopted the SAFE strategy, a comprehensive set of control measures (Surgery for entropion/ trichiasis; Antibiotics for infectious trachoma; Facial cleanliness to reduce transmission; Environmental improvements such as control of disease-spreading flies and access to clean water). The present article reviews the strengths and weaknesses of each component of the strategy. Although significant hurdles remain to be overcome there is every reason to hope that GET 2020 will be successful.